Integrating non-Jewish immigrants and the formation of Israel's ethnic–civic nationhood: from Ben Gurion to the present. Issue 2 (4th March 2017) - Fisher, Netanel; Shilon, Avi
ABSTRACT: The aim of this article is to outline the development of Israel's citizenship and immigration policy from its inception to the present, emphasizing the invaluable role of Israel's first Prime Minister, David Ben Gurion. We argue that through a series of decisions pertaining to civic registration, immigration and naturalization of non-Jews, Ben Gurion set the fundamental principles of modern Jewish nationhood: on the one hand, he rejected the option of establishing a civic-Israeli nation, advocating Jewish-ethnic nationhood instead; on the other hand, this was an inclusive Jewish nationhood which incorporated cultural–territorial elements that were based on a secular interpretation of biblical sources. Despite inserting religious elements into Israel's immigration laws over the years, we claim that Ben Gurion's fundamental principles have for the most part remained in effect until today, constituting the key to understanding the nature of Jewish-Israeli nationhood in our times.